Peran Pengelolaaan Kelas untuk Menumbuhkan Disiplin Belajar dalam Kemampuan Regulasi Diri Siswa Setelah Covid 2019 - Wakhidin, Adwina; Pardimin, Pardimin (Media Manajemen Pendidikan, 2024)
This study aims to describe the role of classroom management after the Covid-19 pandemic in fostering student learning discipline and self-regulation. Using a qualitative method, data were collected through interviews, observations, and documentation from school principals, curriculum coordinators, teachers, and students at SMP N 2 Pakem. Data validity was ensured through triangulation techniques. The findings indicate that classroom management plays a crucial role in maintaining discipline and ensuring smooth learning processes. Key supporting factors include a comfortable learning environment, adequate classroom facilities, and the implementation of rules and effective teaching approaches. Learning discipline is reinforced by displaying school regulations, motivational quotes, and teachers' active role in reminding and guiding students. Self-regulation is reflected in students' ability to set academic goals aligned with minimum competency standards (KKM), study diligently, comprehend lessons seriously, ask teachers for clarification when needed, and seek additional learning materials. These strategies help students improve self-discipline and enhance their learning experience post-pandemic.